THE INTERNATIONAL SELF-DEFENSE INSTITUTE IN THE ERA OF GLOBAL TERRORISM - Oliveira, Rodrigo Szuecs; Augusto da Silva, Carlos Canedo (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The White House legal approach to the War on Terror has been one of the most discussed and least understood topics of international law according to legal counselors of the American government themselves. Despite several speeches and official notes on the subject, the issue remains complex because it involves constitutional rights, human rights and national security. This paper analyzes the War on Terror focusing specifically on the self-defense institute in the world risk society. This means that in order to understand how terrorism is threatening the international order, it is necessary to verify the conceptual changes that determine the self-defense institute and the results of this mutation.